Globalization, Police Reform and Development - Ellison, G. author. aut Link
XII, 258 p.
Keywords: This volume presents a unique examination of Western-led police reform efforts by theoretically linking neoliberal globalization, police reform and development. The authors present seven country case studies based on this theoretical and conceptual approach and assess the prospects for successful police reform in a global context.